Social returns to education in Turkey: Some quantile estimates - (:unkn) unknown (Nova Science Publishers, Inc., 2011)
This paper studies local human capital externalities and returns to education in Turkey. Data comes from 2006 Household Labor Survey. Instrumental Variables-OLS estimation indicates internal (external) returns amounting to 4.9% (2.4%), while IV estimates using quantile regression range from 3% to 6.9% (1.3% to 3.5%). We discuss further characteristics of the Turkish labor market segmented by gender and show that external returns are uniformly higher for women. Our results also indicate both internal and external returns increase or equivalently the wage distribution spreads out as education increases. © 2010 Nova Science Publishers, Inc. All rights reserved.